The Role of Artificial Intelligence in Developing Spatial Thinking in Engineering Graphics Education - Farida Baxtiyorovna Sabirova (Researchparks Publishing, 2026)
This study examines the role of artificial intelligence in developing spatial thinking skills in engineering graphics education. Spatial thinking is considered one of the fundamental competencies for understanding engineering drawings, three-dimensional visualization, and technical design processes. However, traditional instructional approaches often fail to address individual learning differences and difficulties associated with abstract spatial concepts. The proposed conceptual framework integrates adaptive learning technologies, intelligent visualization tools, and automated feedback mechanisms to improve students’ learning experiences. The study is based on constructivist learning theory and cognitive load theory. The findings suggest that artificial intelligence can support personalized learning environments, strengthen spatial reasoning abilities, and improve overall educational effectiveness in engineering graphics education.